WORK IN POLAND DURING THE INTERWAR PERIOD ON THE DESIGNATION OF AN OFFICIAL LANGUAGE FOR THE NORTH CAUCASUS - Adamcevskij, Psemyslav (History, Archeology and Ethnography of the Caucasus, 2020)
The paper aims to analyze the activity of Poland in the interwar period regarding the issues of establishment an independent state in the North Caucasus through separation of it from the Soviet Russia. One issue was in the main focus – attempts at determining which of the languages, spoken in the North Caucasus, should fulfill the function of an official language in case an independent state was created on its territory. The North Caucasus Committee on Languages was assigned to accomplish this task. The commission was founded in 1933 and led by Stanislaw Siedlecki, Chairman of the Eastern Institute in Warsaw and a leading promethean activist. Besides him, a representative of the Ministry of Foreign Affairs of Poland, two professors Olgierd Gurka and Ananiy Zajączkowski, as well as representatives of North Caucasian emigrants, among which were Said Shamil, Bagautdin Hursh, Ibragim Chulik, Urkhan of Tarky, Barasabi Baiytugan, Zhanbek Khavzhoko, Magomed Girei Sunsh, and others joined the committee. As early as at the second meeting, the members came to the conclusion that the Kumyk language is fitted for the official language of the North Caucasus. It was considered as the most widespread language in the region, as well as being similar to those spoken in the neighbouring areas – Azerbaijan, Idel-Ural, Crimea and Turkey. Adyghe language was also qualified for this role, but the idea was abandoned in the end. The reason for it was the fact that, although in the past the Circassians made up the majority of the inhabitants of the North Caucasus, the number of their population decreased significantly after a large emigration in the mid-19th century.The question of designation of the official language for the North Caucasus, which had been raised in Poland in 1930s, suggests that they had ambitious plans regarding the collapse of the Soviet Union. This was a consequence of views of Józef Piłsudski, whose goal was to push Russian borders back to their former state of the Moscovite Rus of the 16th century.
Keywords: prometheism; Poland–Caucasus relations; state language; North-Caucasian emigration; interwar period.